Cross border trade analysis of the rice value chain between Uganda and South Sudan: an insight from Elegu and Nimule border posts - Aluong, Joseph A. Kut; Mainimo, Edmond Nyuyki; Okello, Daniel Micheal; Mugonola, Basil (Informa UK Limited, 2024)
Rice is an important agricultural commodity in Uganda’s economy serving both as cash and food crop and is produced in almost all regions of Uganda. As a cash crop, considerable trade in this commodity occurs within and across the borders of Uganda and South Sudan. Therefore, this study was aimed at conducting a cross border trade value chain analysis between Uganda and South Sudan. Specifically, the rice value chain was analyzed and the determinants of cross border trade were ascertained. Data was analyzed using descriptive statistics and probit regression analysis to determine factors influence cross border trade in rice between Northern Uganda and South Sudan. Results revealed that three quarter of traders were of Ugandans Nationals with significant level (p < 0.001). Econometric model results showed that the source of rice, the nationality of the actor, and business experience (years) and occupation significantly influenced cross border trade. Ugandan traders were involved in trade more than non-Ugandans because of access to locally produced rice. Gender based performance on rice trade was significant (p < 0.002) for both Ugandans and non-Ugandans with males participating in trade more than the females. Most of the wholesale buyers were from Kampala; they buy rice in large volumes while the rest of the rice is bought by exporters, local wholesalers and retailers. Our study recommends that rice value addition and upgrading should be promoted to in order to increase incomes and competitiveness of cross-border trade.